Students’ Attitudes and Motivation towards Learning Literature in English in Zanzibar Secondary Schools - Mosha, Mary A (International Journal of Educational Studies, 2018)
This paper investigated students’ attitudes and motivation towards learning literature in English in three government secondary schools in Zanzibar (one in urban and two in rural areas). The study had a sample of 96 people; 45 boys, 45 girls, and 6 teachers who were teaching literature in English at the selected schools. They were selected through purposive sampling technique. Mixed method was used. Data were collected through interview, observation, and questionnaires. Predictable variables were number of teachers teaching the subject and their qualifications, learning environment, teaching and learning materials, and students’ attitudes and motivation towards learning the subject. Findings revealed that there was shortage of teachers teaching the subject, and some of them were not trained. Students had positive attitudes and motivation towards learning the subject because it was a source of information not only from their own society but also from the world at large. Additionally, literature in English was found a means of entertainment as well as educating the students. However, students’ positive attitudes and motivation towards learning the subject were hindered by unfavourable conditions such as shortage of literature books, difficult English vocabularies, large class sizes, limited time to read suggested literature books, poor teaching methods, and teachers themselves. As a result the study suggests the provision of appropriate and adequate reading materials to all secondary schools, expose teachers to more training so as to be more knowledgeable about various suitable methods of teaching the subject, and improve classroom learning environment.